ANALISIS DAMPAK BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN PADA MOTIVASI DAN KINERJA (STUDI PADA KSPPS BMT NUSA UMMAT SEJAHTERA SEMARANG) - M.Amrullah Reza Putra Tara (ABIS: Accounting and Business Information Systems Journal, 2017)
The long-term goal of this study is about how to management of work motivation from non-financial perspective as a competitive advantage for an organization. Organizational culture is an important foundation for companies to cultivate pride that will represent a good work culture in the future. A strong organization culture will show a high agreement on organizational goals among its members. In addition to organizational culture, leadership is one of the key factors for success or failure of organizing and performing tasks within an organization. Through leadership, formed a unified direction of performance from various individuals within the organization. Organizational culture and leadership style are closely related to motivation, as it becomes a driving force for increased work motivation. High motivation of work will have an impact on the achievement of a company's performance targets. This research was conducted at service organization KSPPS BMT Nusa Ummat Sejahtera Semarang, it was qualitative research which used a case study approach. Data collection techniques used were interviews, observations, questionnaires, and documents. The interviews were conducted on 7 respondents with indepth interview method. The questionnaires were given to 38 respondents with purposive sampling technique. The questionnaire was analyzed using descriptive statistics. The results of this research showed that bureaucratic organizational culture and transactional leadership style had an impact on the low employee motivation and the lack of organizational performance. The employees do not feel involved in a decision-making of bureaucratic organizational culture and the lack of supervisory directive on transactional leadership style of passive management by exception.